Targeted Chemometrics Investigations of Source-, Age- and Gender-Dependencies of Oral Cavity Malodorous Volatile Sulphur Compounds - Kerry L. Grootveld (Data, 2021)
Halitosis is a highly distressing, socially unaesthetic condition, with a very high incidence amongst the adult population. It predominantly arises from excessive oral cavity volatile sulphur compound (VSC) concentrations, which have either oral or extra-oral etiologies (90–95% and 5–10% of cases, respectively). However, reports concerning age- and gender-related influences on the patterns and concentrations of these malodorous agents remain sparse; therefore, this study’s first objective was to explore the significance and impact of these potential predictor variables on the oral cavity levels of these malodorants. Moreover, because non-oral etiologies for halitosis may represent avatars of serious extra-oral diseases, the second objective was to distinguish between etiology- (source-) dependent patterns of oral cavity VSCs. Oral cavity VSC determinations were performed on 116 healthy human participants using a non-stationary gas chromatographic facility, and following a 4 h period of abstention from all non-respiratory oral activities. Participants were grouped according to ages or age bands, and gender. Statistical analyses of VSC level data acquired featured both univariate/correlation and multivariate (MV) approaches. Factorial analysis-of-variance and MV analyses revealed that the levels of all VSCs monitored were independent of both age and gender. Principal component analysis (PCA) and a range of further MV analysis techniques, together with an agglomerative hierarchal clustering strategy, demonstrated that VSC predictor variables were partitioned into two components, the first arising from orally-sourced H2S and CH3SH, the second from extra-orally-sourced (CH3)2S alone (about 55% and 30% of total variance respectively). In conclusion, oral cavity VSC concentrations appear not to be significantly influenced by age and gender. Furthermore, (CH3)2S may serve as a valuable biomarker for selected extra-oral conditions.